KERIPIK KELOR (Moringa oleifera) SEBAGAI PRODUK UNGGULAN DESA KLAMPOKAN, BONDOWOSO, JAWA TIMUR DALAM MENCEGAH STUNTING - Eka Afdi Septiyono; Merina Nuning Dwi; Arum Ayu Puspita (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2021)
Abstract. Kelor (Moringa) is a plant that is still not fully utilized in fulfilling children's nutrition in preventing stunting. Moringa plants are a good source of protein, a source of amino acid phenolics, a source of vitamins, β-carotene, and various essential amino acids. The target of the implementation of the Fostered Villages Community Service program is the Mother PKK group in Klampokan Village. There are 20 members of the PKK Village in Klampokan Village. Klampokan Village is a village that cultivates Moringa, but the utilization is still not optimal, only sold to the market or in private consumption. This service program is carried out in stages of activities, namely observation, counseling on the benefits of Moringa, training, and demonstration of processing Moringa into a commercial product, as well as assistance that will be carried out after the service activities are carried out. The results of the devotion of fostered villages are products in the form of Moringa chips which have economic value and high nutrition, increase the quality and quantity of Moringa chips production by applying appropriate technology, and foster the new independent entrepreneurial spirit in order to increase income and improve welfare in Klampokan Village.               Abstrak. Kelor merupakan tanaman yang masih belum dimanfaatkan secara maksimal dalam pemenuhan gizi anak dalam mencegah stunting. Tanaman kelor merupakan sumber protein yang baik, sumber asam amino fenolat, sumber vitamin, β-karoten, dan berbagai asam amino esensial. Sasaran pelaksanaan Program Pengabdian Desa Binaan ini yaitu kelompok Ibu PKK Desa Klampokan. Anggota Ibu PKK Desa Klampokan berjumlah 20 orang. Desa Klampokan merupakan desa yang membudidayakan kelor, tetapi pemanfaatan masih belum maksimal, hanya dijual ke pasar atau di konsumsi pribadi. Program pengabdian ini dilakukan dengan tahapan kegiatan yaitu observasi, penyuluhan akan manfaat kelor, pelatihan dan demonstrasi pengolahan kelor menjadi produk ekonomis, serta pendampingan yang dilaksanakan pasca kegiatan pengabdian dilaksanakan. Hasil dari pengabdian desa binaan adalah produk berupa keripik kelor yang bernilai ekonomi dan bergizi tinggi, peningkatan kualitas dan kuantitas produksi keripik kelor dengan penerapan teknologi tepat guna, dan menumbuhkembangkan jiwa berwirausaha baru yang mandiri guna menambah pendapatan serta memperbaiki kesejahteraan di Desa Klampokan.